2021
DOI: 10.1038/s41598-021-03003-6
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evidence of remote ischemic conditioning in ischemic stroke, a metanalysis update

Abstract: Remote ischemic conditioning (RIC) is a promising therapeutic approach for ischemic stroke patients. It has been proven that RIC reduces infarct size and improves functional outcomes. RIC can be applied either before ischemia (pre-conditioning; RIPreC), during ischemia (per-conditioning; RIPerC) or after ischemia (post-conditioning; RIPostC). Our aim was to systematically determine the efficacy of RIC in reducing infarct volumes and define the cellular pathways involved in preclinical animal models of ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 82 publications
1
24
1
Order By: Relevance
“…The neuroprotective mechanisms of RIPostC are highly complex and have not been fully elucidated. In addition to attenuation of reperfusion injury [ 80 ], RIPostC has anti-inflammatory [ 81 ], anti-edema [ 69 , 73 , 82 ], angioneurogenic [ 83 ], anti-platelet, and vasodilatory (enhancement of collateral microvascular circulation) effects on ischemic stroke [ 84 , 85 ] that are mediated through numerous neurohumoral chemical messengers, including those released from endothelial-derived exosomes [ 86 ]. The neuronal isoform of NO synthase has also been shown to participate in the neuroprotective effect of RIPostC [ 87 ].…”
Section: Mechanism By Which Ipostc Triggers Endogenous Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuroprotective mechanisms of RIPostC are highly complex and have not been fully elucidated. In addition to attenuation of reperfusion injury [ 80 ], RIPostC has anti-inflammatory [ 81 ], anti-edema [ 69 , 73 , 82 ], angioneurogenic [ 83 ], anti-platelet, and vasodilatory (enhancement of collateral microvascular circulation) effects on ischemic stroke [ 84 , 85 ] that are mediated through numerous neurohumoral chemical messengers, including those released from endothelial-derived exosomes [ 86 ]. The neuronal isoform of NO synthase has also been shown to participate in the neuroprotective effect of RIPostC [ 87 ].…”
Section: Mechanism By Which Ipostc Triggers Endogenous Neuroprotectionmentioning
confidence: 99%
“…The neuronal isoform of NO synthase has also been shown to participate in the neuroprotective effect of RIPostC [ 87 ]. RIPostC protects the brain against cerebral ischemia-reperfusion injury by upregulating endothelial NO synthase through the PI3K/Akt pathway following focal cerebral ischemia in rats [ 85 , 88 ]. RIPostC effectively improved blood-brain barrier permeability by upregulating MMP-9 expression and downregulating claudin-5 expression in a rat model of hypoperfusion caused by severe carotid stenosis [ 80 , 89 ].…”
Section: Mechanism By Which Ipostc Triggers Endogenous Neuroprotectionmentioning
confidence: 99%
“…Remote ischemic conditioning (RIC) represents a new paradigm in neuroprotective therapies (8)(9)(10), and it has the potential ability to protect the ischemic brain from injury until reperfusion and, later, to protect the brain from reperfusion injury (8,11). RIC consists of short and controlled cycles of ischemia-reperfusion applied to one limb during the establishment of cerebral ischemia (perconditioning), before (preconditioning), or after (postconditioning) (11).…”
Section: Remote Ischemic Conditioning (Pre Per and Post) As An Emergi...mentioning
confidence: 99%
“…RIC consists of short and controlled cycles of ischemia-reperfusion applied to one limb during the establishment of cerebral ischemia (perconditioning), before (preconditioning), or after (postconditioning) (11). Until now, the underlying mechanisms of RIC are not clear and there are limited data about the clinical translation of RIPerC in ischemic stroke patients (8,11). Recent trials have only demonstrated the feasibility and safety of this intervention in acute ischemic stroke patients (AIS) (12)(13)(14)(15)(16).…”
Section: Remote Ischemic Conditioning (Pre Per and Post) As An Emergi...mentioning
confidence: 99%
See 1 more Smart Citation